Pendidikan Akhlak Pembinaan Akhlak Siswa: Peran Guru Pendidikan Agama Islam di Madrasah Aliyah Kabupaten Jepara - Safana, Wahilda Nurul Laily; Andriyani, Santi (JOM, 2024)
This study aims to explore in depth the role of Islamic Religious Education (PAI) teachers in shaping the moral character of 11th-grade students at Madrasah Aliyah Masalikil Huda Tahunan Jepara. A qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. The findings reveal that PAI teachers play a significant role in the moral development of students, both through formal teaching methods and by modeling appropriate behavior in daily interactions. The teachers utilize various approaches, such as lectures, interactive discussions, habituation of moral values, and the instillation of Islamic ethics into students' lives. The factors supporting the success of this moral education include the strong commitment of the teachers to set a good example, a curriculum integrated with moral values, and effective collaboration between the school and parents in monitoring student progress. However, the study also identifies several significant challenges. These include the limited time available for PAI teachers to fully integrate moral education and the negative influence of social environments and technology, particularly social media, which often contradicts the moral values taught. This challenge complicates the process of moral education outside the school environment, especially as students are increasingly exposed to contradictory values. The theoretical implications of these findings underscore the importance of integrating moral values across all aspects of education in Islamic institutions to develop a generation with strong moral character, capable of addressing the challenges of the digital age.